Kepemimpinan Transformasional dalam Masa Krisis: Studi Penanganan COVID-19 di Bumi Raja-Raja - Fitriati, Rachma; Marsanty, Dea Alita (Jurnal Bina Praja, 2023)
This study aims to analyze the transformational leadership of Village Heads in efforts to break the chain of the spread of COVID-19 in the Maluku Province area known as Bumi Raja-Raja. Village heads are called "Bapa Raja" because of their position as community leaders, religious leaders, and even traditional leaders because a Bapa Raja must have a noble lineage. This study used a qualitative method with an exploratory and descriptive research approach. Data collection techniques using in-depth interviews, observation and literature review. The results showed that Bapa Raja plays a key role in strengthening local capacity, addressing potential risks, and meeting the basic needs of people in the village. They not only strengthen local empowerment but also overcome and reduce potential and fulfil basic needs in villages by taking concrete action and utilizing local resources pro-actively and having a positive impact in breaking the chain of the spread of COVID-19 and supporting local governments in implementing policies and pandemic response programs. The study recommendation is to strengthen the role of Bapa Raja as a collaborative agent for local governments to increase active community participation in efforts to break the chain of spread of the COVID-19 virus. Thus, in the future, Bapa Raja, as a local leader as well as a traditional & community figure, can be the main force in facing crises while maintaining the stability and prosperity of their community.